ANALISIS FAKTOR RISIKO KEJADIAN ANEMIA PADA IBU HAMIL - Mirnawati Mirnawati; Wa Ode Salma; Ramadhan Tosepu (NHM PRESS, 2022)
Pregnant women who suffer from iron deficiency anemia can have a negative impact on the health of mothers and babies born so that it can increase the maternal mortality rate (MMR) and infant mortality rate (IMR). This study aims to analyze the relationship between the characteristics of the incidence of anemia in pregnant women in the working area of ​​the Kulisusu Public Health Center, North Buton Regency. This cross sectional study was conducted in June-July 2022, in the working area of ​​the Kulisusu Public Health Center, North Buton Regency, involving 126 pregnant women who met the sample criteria. The sampling technique was carried out by simple random sampling. Data analysis using sci square test. The results showed that the frequency of anemia was greater in respondents with normal status than respondents with anemia status (43.7%). The incidence of anemia was related to the age of pregnant women (P-value < 0.000), and not related to income (P-value = 0.602), education level (P-value = 0.225), and gestational distance (P-value = 0.364). The conclusion of the study is that the safe age for pregnant women is between 20-35 years